Actualization of Heutagogy Learning in Islamic Religious Education Learning - Sholihah, Ni'matus; Yusuf, M.; Kusaeri, Kusaeri (MUADDIB Jurnal Kependidikan dan Keislaman, 2024)
Islamic Religious Education (PAI) is an integral part of the education system in many countries with a Muslim majority. To ensure a deep and relevant understanding of religion, effective and contemporary learning methods need to be implemented. An approach gaining attention is heutagogy which promotes independent learning and self-development. This article reviews the concept of heutagogy and its application in the context of PAI learning. Heutagogy teaches students to become independent learners, enabling them to identify their learning needs, plan, initiate, and take full responsibility. This research employs the Systematic Literature Review method, utilizing the Watase Uake tool, EBSCO, Google Scholar, and the Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) technique. Initial research results show that the heutagogical approach can increase students’ motivation, promote a better understanding of the Islamic religion, and prepare them to become moral leaders in society. Focusing on the actualization of heutagogy in PAI learning, this article provides a view on the development of more modern Islamic education, relevant, and attractive to the current students. Incorporating heutagogical elements into PAI learning, schools and educators can help students develop a deeper understanding of their religion, as well as prepare them to face the challenge.